Tezauronimiczny „skarbczyk” sztucznej biżuterii. Kilka uwag o nazwach własnych „drugorzędnych klejnotów” - Węgorowska, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
Imitation jewellery, also known as “secondary gems”, has been people’s companion from antiquity. Its representative objects, however, have rarely been assigned their individualised proper names – thesauronyms. As an answer to the appeal of Polish art historians and museologists: Ewa Letkiewicz, Katarzyna Kluczwajd, Monika Paś and Dorota Zahel, this study is an attempt at a linguistic and culturological presentation of thesauronyms that signify: a pair of earrings, collar, ring, fur fastener clip, necklaces, brooches, duette brooches, jewellery series, collections, lines, sets, limited edition. The attention is also drawn to the specificity of thesauronyms distinguishing similar jewellery items and thesauronyms denoting many various and completely different referents. Moreover, motivation analysis, semantic and motivation analysis, and structural analysis of the names of imitation jewellery names has been conducted. The findings allowed for redefining, verifying, supplementing and extending the term thesauronym.